Aladdin : original Broadway cast recording [compact disc] - Menken, Alan (Walt Disney Records, 2014)
Following in the footsteps of The Lion King and Beauty and the Beast, another beloved Disney classic has made its way the to Broadway stage. Among the cast is Jonathan Freeman, who also served as the voice of Jafar in the original film.